Estudo do desenvolvimento de Masterbaches. - BELLARMINO, Felipe de Oliveira (111, 2015)
Over the years man has applied efforts in research to improve their quality of life. The flexible packaging have been increasing over the years more and more with the increase in processed food , and the bi -oriented polypropylene has been gaining a lot of strength amid the flexible packaging. The objective of this work is to study the mechanical recycling of this polymer : in the quest to answer the following questions : knowledge of the mechanical recycling process and the recycled material can be allocated to the injection process? The hypotheses are that the melt flow rate increases ( the most important point for injection ) with recycling and their properties change , to assign this material to a specific follow-up be it household or even industrial replacing a virgin resin in order to minimize environmental impact . Through the case study and research in books

Over the years man has applied efforts in research to improve their quality of life. The flexible packaging have been increasing over the years more and more with the increase in processed food , and the bi -oriented polypropylene has been gaining a lot of strength amid the flexible packaging. The objective of this work is to study the mechanical recycling of this polymer : in the quest to answer the following questions : knowledge of the mechanical recycling process and the recycled material can be allocated to the injection process? The hypotheses are that the melt flow rate increases ( the most important point for injection ) with recycling and their properties change , to assign this material to a specific follow-up be it household or even industrial replacing a virgin resin in order to minimize environmental impact . Through the case study and research in books
Keywords: Pigmentos; Polimeros industriais; Produção Industrial